Pathology Of “Post-Upper Blepharoplasty Syndrome”: Implications For Upper Eyelid Reconstruction - Steinsapir KD (Dove Medical Press, 2019)
Kenneth D Steinsapir,1 Yoon-Duck Kim2 1Orbital and Ophthalmic Plastic Surgery Division, UCLA Stein Eye Institute, David Geffen School of Medicine at UCLA, Los Angeles, CA, USA; 2Oculoplastic and Orbital Surgery Division, Department of Ophthalmology, Samsung Medical Center, Sungkyunkwan University School of Medicine, Seoul, KoreaCorrespondence: Kenneth D Steinsapir 9001 Wilshire Blvd, Suite 305, Beverly Hills, CA 90211, USATel +1 310 274 7422Fax +1 310 274 7423Email kenstein@ix.netcom.comBackground: The anatomical basis for eyelid changes after upper blepharoplasty is largely uninvestigated. The post upper blepharoplasty syndrome (PUBS) is here defined as upper eyelid ptosis, hollow sulcus, high or absent upper eyelid crease, eyelash ptosis, loose eyelid platform skin, and compensatory brow elevation.Objective: The anatomical basis for the post-upper blepharoplasty syndrome was investigated.Methods: A retrospective, case-controlled, consecutive series of patients was explored for blepharoptosis after cosmetic blepharoplasty (cases) or ptosis surgery (controls). The upper eyelid crease was lowered, blepharoptosis was corrected by anterior levator aponeurosis resection ptosis surgery, eyelash ptosis was corrected with anchor blepharoplasty, and upper eyelid fold volume was restored using anterior orbital fat. Morphologic and anatomical findings were compared between case and control eyelids.Results: Data were available for 42 patients (81 eyelids). Case and control eyelids presented with a clinically similar appearance but internally had a marked difference in their anatomical findings. Eyelids with post-upper blepharoplasty syndrome (n= 24 patients, 48 eyelids) were internally found to have a white-line disinsertion of the levator aponeurosis. The disinserted, central levator aponeurosis was bound into the septal scar created by removal of anterior orbital fat at blepharoplasty. Among the 18 controls (33 eyelids), levator disinsertion was not identified.Conclusion: Hollowness and ptosis in post-upper blepharoplasty syndrome eyelids are related to a white-line disinsertion of the levator aponeurosis and matting of anterior orbital fat in the internal septal scar created during fat removal with blepharoplasty. Knowing where to look for the disinserted central levator is critical to surgically repairing these post-blepharoplasty eyelids.Keywords: eyelid surgery, anchor blepharoplasty, ptosis surgery, cosmetic surgery, Asian eyelid surgery